Anti-Cholinergic Drug Burden Among Ambulatory Elderly Patients in a Nigerian Tertiary Healthcare Facility - Fadare, Joseph O.; Obimakinde, Abimbola Margaret; Aina, Felix O.; Araromi, Ebisola J.; Adegbuyi, Theophilus Adekunle; Osasona, Oluwatoba E.; Agbesanwa, Tosin A. (Frontiers in Pharmacology, 2021)
Background The use of drugs with anticholinergic effects among elderly patients is associated with adverse clinical outcomes. There is paucity of information about anticholinergic drug burden among Nigerian elderly population. Objectives To determine the anticholinergic drug burden among elderly Nigerian patients Methods This was a retrospective cross-sectional study conducted among elderly patients (aged 65 and above) who visited the Family Medicine outpatients’ clinics of the Ekiti State University Teaching Hospital, Ado-Ekiti, Nigeria between July 1 and October 31, 2018. Information extracted from the case files included patient’s age, sex, diagnoses, and list of prescribed medications. Medicines with anticholinergic effects were identified and scored using the anticholinergic drug burden calculator (http://www.acbcalc.com). Results The medical records of 400 patients were analysed with females accounting for 60.5% of the study population. The mean age of participants was 73 ± 7.4 years with only 28 (7%) of patients having more than two co-morbid conditions. Polypharmacy was identified in 152 (38%) of the patients while 147 (36.7%) had drugs with anticholinergic effects prescribed. The anticholinergic burden was high in 60 (15%) patients. Polypharmacy was significantly associated with having more than two diagnosed conditions and high anticholinergic burden (P value of <.001 and .013 respectively). There was significant correlation between total number of prescribed drugs and number of diagnosed conditions (r = .598; p <.000) and between total number of prescribed drugs and number of drugs with anticholinergic effects (r =.196; p<.000). Conclusion The anticholinergic burden in this group of elderly Nigerian patients was low; majority (67%) had no exposure to drugs with anticholinergic effects with only 15% having high anticholinergic burden. Polypharmacy and multiple diagnosed conditions were positively associated with high anticholinergic burden. Based on the positive and significant correlations found in this study, a reduction in the number of prescribed medicines especially those with significant anticholinergic effects used for secondary indications may lessen the anticholinergic burden among the elderly.